Compost amendment, enhanced nutrient uptake and dry matter accumulation in heavy metal stressed maize crop (2014)
Contamination of agricultural lands with heavy metals from industrial activities reduces crop production as a result of poor soil fertility and phytotoxicity. Field trial was conducted to assess the influence of Compost and inorganic fertilizer as well as plant growth stage on growth, nutrient uptake, dry matter accumulation and partitioning in maize crop grown on the battery waste contaminated site. Two types of compost (Mexican Sunflower (MSC) and Cassava peels (CPC) composts) were used for the experiment. These were applied at 0, 20 and 40t/ha to give Control, MSC20, MSC40, CPC20 and CPC40. Inorganic fertilizer (F1: NPK; 20:10:10) at 100kgN/ha was used. 0t/ha serves as check. Sampling was done at one month after planting (1MAP), two (2MAP) and at final harvesting. The results showed that maize plants treated with compost maintained a high rate of photosynthesis and progressively accumulated dry matter more than control and inorganic fertilizer treatments. Addition of MSC40, MSC20, CPC40, and CPC20 increased total dry matter accumulation per plant over that of control by 603.0, 190.9, 354.6 and 148.5% at 1MAP and 8764.30, 4864.3, 4957.1 and 2371.4% at 2MAP respectively. Diversion of dry matter was in favour of the vegetative part (leaf) at 1MAP, root formation at 2MAP and stem and seed formation at harvesting. It was also observed that accumulation was highly significant at 2MAP (which was the period of anthesis and grain filling) and at harvesting compared to 1MAP. At each sampling period, highest total dry matter accumulation was recorded in MSC40. F1 treatment, also increased dry matter accumulation at 1MAP by 41.5% but reduced it by 21% at 2MAP compared to control. All the maize plants on F1 and control were uprooted at 2MAP when they started dying back. Compost also increased the concentrations of calcium, magnesium, potassium and phosphorous in the maize plants compared to control with MSC40 being superior to other treatments. Nutrients accumulation was significant at harvesting. Phosphorous concentration was high in the seeds of the harvested maize plants than other plant parts. Enrichment with Compost had ameliorative effect on maize grown on Pb contaminated soil and increased nutrient and dry matter accumulation in actively growing maize crop on heavy metal contaminated soil. Assimilate accumulation and partitioning was a function of maize growth stage and soil nutrient status.